2020
DOI: 10.1080/14737159.2020.1865806
|View full text |Cite
|
Sign up to set email alerts
|

Predicting wet age-related macular degeneration (AMD) using DARC (detecting apoptosing retinal cells) AI (artificial intelligence) technology

Abstract: Cordeiro (2020): Predicting wet age-related macular degeneration (AMD) using DARC (detecting apoptosing retinal cells) AI (artificial intelligence) technology, Expert Review of Molecular Diagnostics,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In later years, a convolutional neural network (CNN) based on template matching was developed for the fully automated assessment of DARC images (Normando et al, 2020). In addition to offering full automation of counting, the accuracy of this CNN based approach allowed for precise discrimination between stable and progressive or high risk eyes (Corazza et al, 2020;Normando et al, 2020).…”
Section: Automated Counting Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In later years, a convolutional neural network (CNN) based on template matching was developed for the fully automated assessment of DARC images (Normando et al, 2020). In addition to offering full automation of counting, the accuracy of this CNN based approach allowed for precise discrimination between stable and progressive or high risk eyes (Corazza et al, 2020;Normando et al, 2020).…”
Section: Automated Counting Methodsmentioning
confidence: 99%
“…(Schmitz-Valckenberg et al, 2010) In a mouse retinal ischaemic model, histological demonstration of annexin A5 positivity in inner nuclear, outer nuclear and photoreceptor has been demonstrated following intravitreal administration in vivo of Alexa Fluor 488-annexin (Normando et al, 2013a). More recent work has identified that DARC staining in a rabbit model of wet AMD localises to endothelial cells (Corazza et al, 2020).…”
Section: Verifying the Darc Signal In Amd Modelsmentioning
confidence: 98%
See 3 more Smart Citations